Strategies of Dose Escalation in the Treatment of Locally Advanced Non-Small Cell Lung Cancer: Image Guidance and Beyond - Chi, Alexander; Nguyen, Nam Phong; Welsh, James S.; Tse, William; Monga, Manish; Oduntan, Olusola; Almubarak, Mohammed; Rogers, John; Remick, Scot C.; Gius, David (Frontiers in Oncology, 2014)
Radiation dose in the setting of chemo-radiation for locally advanced non-small cell lung cancer (NSCLC) has been historically limited by the risk of normal tissue toxicity and this has been hypothesized to correlate with the poor results in regard to local tumor recurrences. Dose escalation, as a means to improve local control, with concurrent chemotherapy has been shown to be feasible with three-dimensional conformal radiotherapy in early phase studies with good clinical outcome. However, the potential superiority of moderate dose escalation to 74 Gy has not been shown in phase III randomized studies. In this review, the limitations in target volume definition in previous studies; and the factors that may be critical to safe dose escalation in the treatment of locally advanced NSCLC, such as respiratory motion management, image guidance, intensity modulation, FDG-PET incorporation in the treatment planning process, and adaptive radiotherapy, are discussed. These factors, along with novel treatment approaches that have emerged in recent years, are proposed to warrant further investigation in future trials in a more comprehensive and integrated fashion.